Dual efficacy-toxicity of Chelidonii Herba in chronic obstructive pulmonary disease: Integrated network pharmacology, immune profiling and molecular docking - Guoliang Chen; Tianqing Wang (PLoS ONE, 2025)
Objective To investigate the pharmacodynamic material basis, multi-target mechanisms of Chelidonii Herba in treating chronic obstructive pulmonary disease (COPD), and its hepatotoxicity pathways using network pharmacology, network toxicology, and molecular docking. Methods Active components and targets of Chelidonii Herba were screened via Traditional Chinese Medicine Systems Pharmacology (TCMSP), SwissTargetPrediction (STP), and PharmMapper databases. COPD and hepatotoxicity targets were obtained from GeneCards and OMIM. Venn diagrams identified shared targets. Protein-protein interaction (PPI) networks were constructed using STRING, with core targets filtered via CytoNCA. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed in Metascape. Molecular docking was validated by AutoDock Vina, and immune infiltration was analyzed using the GSE55962 dataset. Results Twenty active components and 108 potential targets of Chelidonii Herba were identified. Eighty shared targets intersected with COPD, and 96 with hepatotoxicity. Seven core targets for COPD treatment (CASP3, PPARG, PTGS2, CDK2, ALB, HSP90AA1, ESR1) and hepatotoxicity (PPARG, ESR1, CASP3, PTGS2, ESR2, CALM3, ALB) were determined. KEGG enrichment revealed COPD mechanisms involving PI3K-Akt, VEGF, and cGMP-PKG pathways, while hepatotoxicity implicated VEGF, PI3K-Akt, and estrogen signaling. Core components (e.g., dihydrochelerythrine, oxysanguinarine) exhibited strong binding to targets (binding energy ≤ −5.0 kcal/mol, partial ≤ −7.0 kcal/mol). Immune infiltration analysis linked core targets to macrophages M2 and γδ T cells. Conclusion Chelidonii Herba treats COPD primarily through alkaloids modulating shared targets (CASP3, PPARG, PTGS2) via PI3K-Akt pathways, while concurrently inducing hepatotoxicity through VEGF and estrogen signaling. This dual efficacy-toxicity profile necessitates cautious clinical application and experimental validation to define safe therapeutic windows.